3D Printed Bone Scaffolds: Delivering Proangiogenic Factors from 3D‐Printed Polycaprolactone Scaffolds for Vascularized Bone Regeneration (Adv. Healthcare Mater. 23/2020). Issue 23 (2nd December 2020) - Liu, Haoming; Du, Yingying; Yang, Gaojie; Hu, Xixi; Wang, Lin; Liu, Bin; Wang, Jianglin; Zhang, Shengmin
Abstract : In article number 2000727 by Bin Liu, Jianglin Wang, Shengmin Zhang, and co‐workers, a porous 3D scaffold is developed via a microsphere‐based 3D printing technique. An angiogenic growth factor, VEGF, is immobilized on the scaffold by coprecipitation and is able to facilitate vascularized bone regeneration in vivo. This biomineralization/coprecipitation approach provides a paradigm for engineering 3D scaffolds with susceptible growth factors/genes in physiological conditions.